Needle fracture during endoscopic ultrasound-guided fine needle aspiration using a needle with a side hole - Sasaki, Takashi; Kanata, Ryo; Sasahira, Naoki (Endoscopy International Open, 2018)
Background and study aims Endoscopic ultrasound-guided fine needle aspiration (EUS-FNA) is widely performed to obtain pathological evidence from several parts of the body. Major complications of EUS-FNA are bleeding, pancreatitis, and abdominal pain. Needle fracture is a rare complication of EUS-FNA and only a few relevant reports are available. Here, we report a case of needle fracture during EUS-FNA using a needle with a side hole. A 61-year-old man underwent EUS-FNA of the uncinate process of the pancreas to confirm malignancy. A 20-gauge needle with a side hole was used to puncture the mass from the first part of the duodenum. The needle fracture occurred at the side hole during the third passage, and the fragment remained in the pancreas. Fortunately, the patient did not exhibit any symptoms due to the needle fragment. This case indicates that repeated puncture using the same needle with a side hole might increase risk of needle fracture during EUS-FNA. It is important to inform clinicians about the potential risk of needle fracture, particularly given the increasing number of EUS-FNAs being performed.